The Escazú Agreement and the Protection of Environmental Human Rights Defenders - Pánovics, Attila (Pécs journal of international and European law, 2021)
The Regional Agreement on Access to Information, Public Participation and Justice in Environ- mental Matters in Latin America and the Caribbean, better known as the Escazú Agreement, en- tered into force on 22 April 2021, coinciding with International Mother Earth Day celebrations. The Escazú Agreement constitutes the first environmental treaty ever concluded under the auspices of ECLAC, and the first in the world to contain specific provisions on human rights defenders in environmental matters. Hopefully, the entry into force of the Escazú Agreement and its implemen- tation at the national level will contribute significantly to the protection of the environment, and environmental, land and indigenous defenders.